2002
DOI: 10.1038/sj.onc.1205048
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL and inhibitors of apoptosis are opposing determinants for NF-κB-dependent, genotoxin-induced apoptosis of cancer cells

Abstract: Opposing pro-and anti-apoptotic actions of TRAIL and the inhibitors of apoptosis (IAPs) contribute to the cell's decision to survive or die. We demonstrate that in H157 human lung carcinoma cells, etoposide and doxorubicin induce the NFkB-dependent expression of both pro-and anti-apoptotic proteins including TRAIL and its death receptor, DR5, and IAPs. Inhibition of NF-kB activation in H157 cells in response to genotoxin resulted in loss of cell surface expression of TRAIL and DR5, aggressive growth and chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…NF-B is first activated at early times after reovirus infection, an event that is required for apoptosis in both TRAIL-sensitive and TRAIL-resistant cells and which presumably acts to up-regulate the expression of pro-apoptotic NF-B-regulated genes. Both TRAIL and its receptors are regulated by NF-B (32)(33)(34). It is, thus, likely that the pro-apoptotic effects of NF-B activation that are required for reovirusinduced apoptosis include the up-regulation of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…NF-B is first activated at early times after reovirus infection, an event that is required for apoptosis in both TRAIL-sensitive and TRAIL-resistant cells and which presumably acts to up-regulate the expression of pro-apoptotic NF-B-regulated genes. Both TRAIL and its receptors are regulated by NF-B (32)(33)(34). It is, thus, likely that the pro-apoptotic effects of NF-B activation that are required for reovirusinduced apoptosis include the up-regulation of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] However, the mechanisms leading to TRAIL sensitivity are controversial. 5,[34][35][36][37][38][39][40][41] Upregulation of the apoptosis-inducing TRAIL receptors after treatment with 5-fluorouracil (5-FU) has been implicated in sensitising human leukaemic and glioma cells. 31,35 Bernard et al 42 presented data supporting the role of TRAIL-R3 and TRAIL-R4 as putative decoy receptors, preventing apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our previous data 43 showed that MEN 10755 did not induce proapoptotic NF-B target genes such as TRAIL and TNFR. 37 The observed downmodulation of c-myc expression could be directly linked to topo II poisoning since gene-specific cleavage sites in the c-myc promoter and first exon have been described. 44,45 Therefore, we found in MEN 10755-treated A2780 cells a pattern of gene modifications that can lead to cell death, with no evidence of prosurvival gene expression ascribable to NF-B activity.…”
Section: Discussionmentioning
confidence: 99%
“…To better clarify this point, we checked whether other NF-B target genes were activated in A2780 cells by MEN 10755 treatment. We chose 5 genes (A1, A20, MnSOD, IEX-1L and c-myc) described as antiapoptotic in different cell types 21,[37][38][39] and analyzed their expression by RT-PCR. We detected basal expression of A20, Mn-SOD, IEX-1L and c-myc (Fig.…”
Section: Gene Activation Pattern In A2780 Cells In Response To Men 10mentioning
confidence: 99%